Determination of soil volume by planialtimetric survey methods - Vanzela, Luiz S.; Araujo, Osvaldo [UNESP]; Lima, Ronaldo C. [UNESP] (FapUNIFESP (SciELO), 2020)
Considering the importance of topographic surveys to determine soil volumes and study efficient and accessible alternatives for this operation, this study aimed to analyze methods and respective equipment for planialtimetric surveys to determine soil volume. An experimental grid was installed in an area locate in Fernandopolis, SP, Brazil, in which quotas were measured by geometric leveling (standard method), trigonometric leveling, leveling with receivers of the Global Navigation Satellite System (GNSS) by relative (frequencies L1/L2) and absolute positioning (code C/A) and extraction of altitudes in digital terrain model from SRTM and ASTER images. In comparison to geometric leveling, trigonometric leveling was the most accurate in determining soil volume (0.6% error), followed by GNSS leveling by relative positioning (23.7% error), and extraction of altitudes by SRTM (32.0% error) and ASTER images (38.3% error). GNSS leveling by absolute positioning presented the highest error in determining soil volume (287.4%) compared to the other methods.
Keywords: Geomatics; Geometric leveling; GNSS; Trigonometric leveling